Association Between Vitamin D Binding Protein Gene Polymorphism (rs7041), Vitamin D Receptor, and 25-Hydroxyvitamin D Serum Levels With Prostate Cancer in Kurdish Population in West of Iran - Mohammad Amiri; Daniel Elieh Ali Komi; Asad Vaisi-Raygani; Amir Kiani; Mahmoudreza Moradi; Mahdieh Aliyari; Zohreh Rahimi; Ehsan Mohammadi-Noori; Homayoon Bashiri (Frontiers Media S.A., 2022)
Prostate cancer (PCa) pathology has been linked to vitamin D, vitamin D receptors (VDRs), and vitamin D binding proteins (VDBPs). We sought to investigate the association between VDR rs2228570 and rs1544410 as well as VDBP rs7041 polymorphisms and serum 25-hydroxyvitamin D (25(OH)-vitamin D) levels in PCa patients. Blood samples were collected from 111 PCa patients and 150 age-matched healthy volunteers. The VDR rs2228570 T/C, rs1544410 G/A, and VDBP rs7041 T/G genotypes were determined using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). 25(OH)-vitamin D and PSA (Total and Free) serum levels were measured. The frequencies of VDBP genotypes T/G vs. T/T (56.5% vs. 44.5%, p = 0.01) according to the dominant model T/G + G/G vs. T/T (84.3% vs. 71.5%, p = 0.01) were significantly higher in PCa patients when compared to control group and considerably increased the risk of disease by 2.29, 1.44, and 2.13 folds respectively. Interestingly, the results demonstrated that PCa patients with the dominant model (T/G + G/G vs. T/T) of VDBP had significantly lower serum levels of vitamin D and higher serum levels of total and free PSA in comparison to the controls. Furthermore, when compared to controls, PCa patients with the dominant model T allele (T/G + G/G vs. TT) of VDBP had significantly higher vitamin D, total PSA, and free PSA concentrations. Serum levels of 25(OH)-vitamin D and rs7041 T/G polymorphism of the VDBP gene could be potential risk factors for PCa.